2020
DOI: 10.1002/aenm.202003243
|View full text |Cite
|
Sign up to set email alerts
|

Conductor‐Free Anode of Transition Metal Dichalcogenide Nanosheets Self‐Assembled with Graft Polymer Li‐Ion Channels

Abstract: The development of anodes for lithium‐ion batteries (LIBs) based on liquid‐phase‐exfoliated 2D transition metal dichalcogenide (TMD) nanosheets has been studied extensively because their intrinsic capacity is higher than graphite. Since most semiconducting TMDs possess low electrical conductivity and lithium‐ion diffusivity, expensive processes are necessary such as the addition of conductive fillers, chemically converted metallic phase transformation, and topological nano‐fabrication. Here, a novel conductor‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Sulfonated poly(styrene) (SPS) ionomers were grafted onto poly(vinylidene fluoride- co -trifluoroethylene) (PVDF-TrFE) for MoS 2 electrodes. 95 The SPS formed ionic channels by self-assembly to facilitate ionic transport. At a current density of 0.5 A g −1 , MoS 2 with PVDF-TrFE- g -SPS binders delivered a discharge capacity of 862.0 mA h g −1 and retained 91.0% capacity after 1000 cycles compared with a 450.1 mA h g −1 discharge capacity and ≈69% capacity retention of PVDF-TrFE binders.…”
Section: Functionality Of Binders In Libsmentioning
confidence: 99%
“…Sulfonated poly(styrene) (SPS) ionomers were grafted onto poly(vinylidene fluoride- co -trifluoroethylene) (PVDF-TrFE) for MoS 2 electrodes. 95 The SPS formed ionic channels by self-assembly to facilitate ionic transport. At a current density of 0.5 A g −1 , MoS 2 with PVDF-TrFE- g -SPS binders delivered a discharge capacity of 862.0 mA h g −1 and retained 91.0% capacity after 1000 cycles compared with a 450.1 mA h g −1 discharge capacity and ≈69% capacity retention of PVDF-TrFE binders.…”
Section: Functionality Of Binders In Libsmentioning
confidence: 99%
“…Alternatively, Park and colleagues reported an exfoliated 2D TMD (MoS 2 ) nanosheets with interlayer channels of ≈1 nm for LIBs, which delivered a high specific capacity of 933.1 mA h g −1 at 0.1 A g −1 and excellent cycling stability with 90% retention after 1000 cycles. 633 The SNPCs between the layers with good tolerance to volume expansion and negatively charged channels for fast ion transportation were attributed to the enhancement of the electrochemical performance. It has also been reported that Ni 2 P anchored in nitrogen doped carbon (Ni 2 P@N–C) with rich SNPCs could deliver enhanced rate capability (197 mA h g −1 at 2 A g −1 ) and excellent cycling stability (0.06% capacity decay per cycle), as a result of the high electrical conductivity of the matrix and confinement effect of the SNPCs (Fig.…”
Section: Electrochemical Couplings In Snpcsmentioning
confidence: 99%
“…Therefore, this triggers a continuous search enthusiasm for seeking alternative anode materials to graphite. So far, various types of materials have sprung up like mushrooms, such as carbon materials, 1,2 non-metallic elements (Si, P), 3,4 transition metal dichalcogenides (TMDCs), 5,6 transition metal oxides (TMOs), 7,8 and transition metal nitrides (TMNs). 9,10 Particularly, TMOs have attracted considerable attention due to their high theoretical specific capacity via multielectron reactions and easy preparation with controllable morphology.…”
Section: Introductionmentioning
confidence: 99%